Right ventricular function and anemia in heart failure with preserved ejection fraction - Wang, Jia; Jiang, Jiahui; Li, Xiang; Tan, Xilun; Zhou, Yanni; Luo, Ze; Wang, Xuesen; Zhao, Xuezhu; Liu, Yiying; Wang, Ming; Zhang, Chenhao (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAnemia is a common complication in patients with heart failure and is associated with left ventricular systolic dysfunction. However, its role in right ventricular (RV) function has not been evaluated.MethodsWe retrospectively analyzed the electronic medical data of 1,014 Heart Failure with Preserved Ejection Fraction (HFpEF) patients to evaluate the relationship between anemia and RV dysfunction in patients with HFpEF and whether this relationship is influenced by classical risk factors such as smoking and hypertension.ResultsThe study showed that anemic patients were older and had significantly higher New York Heart Association functional class and tricuspid regurgitation (TR) than non-anemic patients. The level of hemoglobin (Hb) had a weak negative linear correlation with NT-pro-BNP (log-transform, r = 0.30, P < 0.0001) and a positively correlation with the tricuspid annular plane systolic excursion (TAPSE)/pulmonary arterial systolic pressure (PASP) ratio (r = 0.44, P < 0.0001). Multivariate linear regression analysis shows that the degree of anemia, atrial fibrillation, and TR were independently associated with the TAPSE/PASP ratio.ConclusionAnemia in HFpEF is associated with RV dysfunction, and this relationship is not affected by classical risk factors, such as smoking, hypertension, and diabetes.